2016
DOI: 10.1186/s12890-016-0296-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development of pulmonary arterial hypertension in Australian systemic sclerosis patients: results from a large multicenter cohort study

Abstract: BackgroundPulmonary arterial hypertension (PAH) is the leading cause of mortality in patients with systemic sclerosis (SSc). We sought to determine the incidence, prevalence and risk factors for PAH development in a large Australian SSc cohort.MethodsPAH was diagnosed on right heart catheterisation (mPAP >25 and PAWP <15 mmHg at rest). Patients with PH secondary to interstitial lung disease (ILD; defined as abnormal HRCT scan and FVC < 60 %) were excluded. Summary statistics, chi-square tests, univariate and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 34 publications
1
16
0
7
Order By: Relevance
“…common among patients with diffuse cutaneous subtype than among those with limited subtype. The prevalence of pulmonary hypertension (10.1%) found here is also close to that reported in previous series [3,11,39,40].…”
Section: Discussionsupporting
confidence: 92%
“…common among patients with diffuse cutaneous subtype than among those with limited subtype. The prevalence of pulmonary hypertension (10.1%) found here is also close to that reported in previous series [3,11,39,40].…”
Section: Discussionsupporting
confidence: 92%
“…As predictive factors for PAH, its incidence was higher in SSc patients with ILD. 27 Conversely, another study reported no association between the severity of ILD and the right atrial pressure measured via right catheterization in SSc patients, suggesting that the pulmonary fibrotic changes in the ILD of SSc differ from those of the pulmonary vascular pathophysiology in PAH. 28 Clinically, combined PAH in SSc patients with ILD leads to a large difference in the prognosis compared to that in SSc patients with ILD only.…”
Section: Discussionmentioning
confidence: 97%
“…Изменения кожи по типу отека или атрофии в большей степени ассоциируются с ЛАГ, чем диффузное поражение. Тем не менее в части работ среди пациентов с ЛАГ имеется весомая доля больных с диффузной клинической формой [20]. Вероятно, причиной подобного несоответствия является включение в исследование пациентов с интерстициальным поражением легких (ИПЛ), так как известно, что это висцеральное проявление ССД более характерно для диффузной клинической формы [21].…”
Section: классификация легочной гипертензии (ниццаunclassified
“…Это утверждение, помимо классификационной путаницы, приводит к курьезным результатам, взаимоисключающим друг друга. Так, в двух работах [20,22] Другое клиническое проявление ССД, очень часто выявляемое у больных ЛАГ, -телеангиэктазии [24]. Клинический симптом, которому ранее уделялось достаточно мало внимания, в последние годы показал свою значимость в диагностике и оценке прогноза.…”
Section: классификация легочной гипертензии (ниццаunclassified